Sistem maklumat keluar masuk penghuni asrama SMK Kuala Krau menggunakan Mykad dan aplikasi mobile - Norazlilah, Khamdan (2010)
Sistem Maklumat Keluar Masuk Penghuni Asrama SMK Kuala Krau Menggunakan MyKad dan Aplikasi Mobile (SMAKK) is system which developed in order to / replace current system at Sekolah Menengah Kebangsaan (SMK) Kuala Krau hostel. Currently, manual registration is use in SMK Kuala Krau hostel for students movement, where students have to record their movement details on the log book. The problem in the current system are, the possibility of losing students record data due to losing the log book or misplacement of it. In this manual system, warden have problem to keep track the student movement because warden have to manually analyse each record one by one. Therefore, SMAKK is develop to overcome the problem. This system is able to record student information by using Malaysia Government Multipurpose Card (MyKad). This system able to capture date and time when student register in/out. In/out information are recorded in a database, which provides data manipulation and report generating. The benefits of this system are to provide organized view of student records and reducing the time spent on managing student in/out information and can be access using PDA which can help warden to monitoring in/out activities easily.